2022
DOI: 10.1108/cc-03-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Returns on library investment: seeking causative relationship between the library investment and the institutional research output

Abstract: Purpose This study aims to seek the causative relationship between the library budget and research output with the ranking of 20 leading medial institutes in India. More so, the study also attempts to find out whether the libraries associated with academic and research institutes in general and medical institutes in particular have turned redundant or irrelevant, or have become more relevant in the changing times by embracing technology in its every new form. Design/methodology/approach The study is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Research underscores the importance of investment in education. For instance, research has demonstrated that funding or financial aid is critical to the survival, excellence and sustenance of research institutions (Singh, et al, 2023). Research in medical education has further shown that whereas investing in scholarship and educational innovation remains essential for excellence, funds for educational development and innovations are put at risk since they hardly generate offsetting revenue (Poncelet, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Research underscores the importance of investment in education. For instance, research has demonstrated that funding or financial aid is critical to the survival, excellence and sustenance of research institutions (Singh, et al, 2023). Research in medical education has further shown that whereas investing in scholarship and educational innovation remains essential for excellence, funds for educational development and innovations are put at risk since they hardly generate offsetting revenue (Poncelet, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%